Effect of company size ownership concentration auditor reputation board of commissioners and risk management committee on disclosure of enterprise risk management - Achmad Qulyubi; Eko Suprayitno; Nur Asnawi; Segaf Segaf (Institute of Computer Science (IOCS), 2023)
In the business world, companies are expected to be able to reduce the impact of risks faced by the companies themselves, and one of the aspects is risk management, but in reality, there are still many companies that have not disclosed their risk management in their annual reports, including a financial company. Financial companies are required by the government to report risk disclosure in their financial statements, but in practice, there are still many financial companies that disclose risk voluntarily. The purpose of this study is to assess company size, the concentration of ownership, the reputation of auditors, the board of directors, risk management committee on enterprise management disclosures. The data used is data obtained from the website. www.idx.co.id . Fifty companies were selected using the target sampling method. This survey was conducted from 2017 to 2020, so the data volume for this survey is 200 data. The analytical method used is multiple regression analysis using SPSS version 24, and this study found that the board of directors and the risk management committee influence the company's risk management disclosures. Company size, concentration of ownership, and audit reputation do not affect the disclosure of company risk management.